DETERMINAN KEJADIAN ISPA NON PNEUMONIA PADA ANAK BALITA DI KELURAHAN KEDUNG SARI KECAMATAN SUKAJADI KOTA PEKANBARU - Christine Vita Gloria Purba; Okta Safryanni; Al Hidayati; Zulmeliza Rasyid (Jurnal Penelitian Kesmasy, 2019)
Non pneumonia Acute Respiratory Tract Infection (ARI) is a respiratory tract disease that is acute with a cough that does not show symptoms of increased respiratory frequency and does not indicate the pull of the lower chest wall inward. The incidence of non pneumonia ARI in children under five in Kedung Sari Village was recorded at 40.06%. This study aims to determine the description and determinant of the incidence of non-pneumonia ARI in children under five in Kedung Sari Village, Sukajadi District, Pekanbaru City in 2019. This type of research is quantitative observational analytic with cross sectional design. The study population was all children under five who lived in Kedung Sari Village, Sukajadi District, Pekanbaru City, amounting to 312 people with a sample of 172 respondents. The sampling technique was done by consecutive sampling. The type of data used in this study are primary data and secondary data by means of retrieving data through measurements and questionnaires. Data analysis was done by univariate and bivariate with chi square test. The results showed that there was a correlation between exposure to cigarette smoke (p-value 0,000) and the incidence of non-pneumonia ARI in children under five. It is expected that health workers, especially in the health promotion section of the community health center in implementing control and eradication programs of Acute Respiratory Tract Infection can provide health education, especially regarding the dangers of cigarette smoke for children under five and recommend smokers to smoke in special places so children under five are not exposed cigarettes.